Trendy brands: What makes a brand perceived as trendy - Vieira, J.; Bicho, M. (Journal of Brand Management)
Consumers perceive certain brands as trendy, thereby rendering them more desirable than those that are considered untrendy. Although it is common to observe its use by academics and consumers, the meaning and context in which trendy is used are often unclear and ambiguous. This study seeks to address this gap. Employing an abductive approach and thematic analysis, a multi-method and qualitative investigation was undertaken. The data collection involved three focus groups and two sets of interviews. Our findings led to advance a definition and the development of a conceptual framework for trendy brands. Still, our study identified a ‘trendy brands journey’ illustrating how trendy brands evolves over time. Our findings contribute to branding and brand equity theory by suggesting a new brand determinant: trendy brands. This research may hold particular significance for companies’ management. By incorporating trendy attributes into their branding strategies, companies could leverage brand loyalty, purchase intentions and the willingness to pay premium prices by consumers.